2021
DOI: 10.1097/pts.0000000000000350
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Measurement Tools for the Proactive Assessment of Patient Safety in General Practice

Abstract: Background. Primary care physicians have reported a difficulty in understanding how best to measure and improve patient safety in their practices. Objectives. To identify measures of patient safety suitable for use in primary care and provide guidance on proactively monitoring and measuring safety. Methods. Searches were conducted using Medline, Embase, CINAHL and PsycInfo in February 2016. Studies that utilised a measure assessing levels of, or attitudes towards, patient safety in primary care were considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 68 publications
1
29
0
Order By: Relevance
“…They found 21 articles, including a total of 182 safety measures, and classified these into six dimensions: (1) medication management, (2) sentinel events, (3) care co-ordination, (4) procedures and treatment, (5) laboratory testing and monitoring and (6) facility structures/resources. However, the types of measures were not dissimilar to those found by Lydon et al 47 An earlier review by Ricci-Cabello et al 49 undertook a similar exercise and reached similar conclusions (albeit on a smaller scale). Therefore, the inclusion of patient safety within a broader index will pose a significant challenge.…”
Section: Overall Performance Measurementsupporting
confidence: 54%
See 1 more Smart Citation
“…They found 21 articles, including a total of 182 safety measures, and classified these into six dimensions: (1) medication management, (2) sentinel events, (3) care co-ordination, (4) procedures and treatment, (5) laboratory testing and monitoring and (6) facility structures/resources. However, the types of measures were not dissimilar to those found by Lydon et al 47 An earlier review by Ricci-Cabello et al 49 undertook a similar exercise and reached similar conclusions (albeit on a smaller scale). Therefore, the inclusion of patient safety within a broader index will pose a significant challenge.…”
Section: Overall Performance Measurementsupporting
confidence: 54%
“…However, patient safety within primary care is not something that is measured in any standard form. Lydon et al 47 conducted a systematic review of measurement tools for the proactive assessment of patient safety in general practice. Of the 56 studies identified by this systematic review, 34 used surveys/ interviews, 14 used a form of patient chart audit and 7 used practice assessment checklists; there were a handful of other tools that were not repeated across studies.…”
Section: Overall Performance Measurementmentioning
confidence: 99%
“…Scores on the QATSDD can range from 0 to 42 (qualitative and quantitative studies) or 48 (mixed‐methods studies). This assessment tool has been shown to produce good agreement and has been used in a number of different reviews pertaining to health services and medical education research . The QATSDD was applied to studies within both categories by two researchers independently and any disagreements were resolved through discussion.…”
Section: Methodsmentioning
confidence: 99%
“…This tool was considered appropriate as the studies included in this review were heterogeneous in design. The QATSDD is a 16-item scale developed for use by health service researchers, which has been used successfully in other systematic reviews (25)(26)(27). Each QATSDD item is scored on a scale ranging from 0 (e.g., 'no mention at all') to 3 (e.g., 'detailed description of each stage of the data collection procedure'), with a maximum possible score of 42 for qualitative or quantitative studies, and 48 for mixed method studies.…”
Section: Methodological Qualitymentioning
confidence: 99%